Neck circumference measurement as a screening tool for obesity in children - H. T., Yashoda; B., Swetha; A. S., Goutham (International Journal of Contemporary Pediatrics, 2017)
Background: Childhood obesity is a rising epidemic and a major public health problem with the risk for type 2 diabetes mellitus, hypertension and cardiovascular disorders in later life. Neck circumference (NC), a marker of upper body subcutaneous adipose tissue distribution can predict higher metabolic risk. The aim of the present study was to evaluate the association between neck circumference (NC) and obesity. Methods: This cross-sectional prospective observational study was conducted in Bangalore in the month of October 2016. 172 male and 161 female students, aged 13-17 years were screened. Anthropometric markers of obesity measured included body mass index (BMI), waist circumference (WC), hip circumference (HC), waist-to-hip ratio (WHR), and compared with neck circumference (NC) of the same subjects. Pearson’s correlation coefficient was calculated between neck circumference and other obesity indices, and receiver operating characteristic curve analysis was used to determine the best cutoff value of neck circumference in predicting high BMI. Results: Overall, 13.2% boys and 9.9% girls were found overweight/obese. The mean BMI was 25.27±2.09kg/m2 and25.17±2.23kg/m2, mean neck circumference was 33.43±2.3cm and 31.50±1.4 in overweight/obese boys and girl respectively. All of the anthropometric parameters were found to be significantly higher in overweight/obese children than with their normal weight peers and higher in boys compared to girls. The neck circumference in boys was significantly greater than girls and higher in overweight/obese with P<0.001. The best cut-off value of neck circumference by ROC to identify boys with a high BMI was 32cm with sensitivity of (81.82%), specificity (89.06%), and for girls was 30cm with sensitivity of (84.85%), specificity (87.5%). Neck circumference had a strong positive correlation with other anthropometric measures BMI, WC, waist hip ratio in both boys and girls (p <0.001). Conclusions: Neck circumference significantly correlated with other indices of obesity. It can be used with great reliability to screen overweight and obesity in children. NC can be considered as a simple, time saving and inexpensive clinical tool for detection of obesity in large population-based studies in children and adolescents.